Does Digital Pedagogy Matter for EFL Writing? Cybergogy, Student Engagement, and High School Students’ Writing Skills - Suryadi; Feby Charlos (Universitas Hamzanwadi, 2026)
Writing remains one of the most demanding skills in EFL learning because it requires students to coordinate linguistic accuracy, idea development, organization, and sustained cognitive effort. In digitally mediated learning contexts, effective pedagogy and students’ active engagement may play important roles in supporting writing development. This study examined the correlations among cybergogy, student engagement, and English writing skills among high school students in Serang City, Indonesia. Using a quantitative correlational design, the study included 330 Grade XI students selected from a population of 1,887. Data were collected using a validated 12-item questionnaire with a five-point Likert scale and analyzed in SPSS 26. The analysis included normality testing, Pearson correlation, t-tests, ANOVA, and coefficient of determination. The findings showed that cybergogy was significantly and positively correlated with students’ writing skills (r = 0.564, p < 0.001), whereas student engagement showed a stronger positive correlation (r = 0.688, p < 0.001). Simultaneously, cybergogy and student engagement were significantly associated with writing skills (R = 0.763, R² = 0.582, F = 151.121, p < 0.001), explaining 58.2% of the variance in students’ writing skills. These results indicate that EFL writing development is associated not only with the quality of digitally mediated pedagogy but also with students’ behavioral, emotional, and cognitive engagement. The study implies that English teachers should design digital writing instruction that combines structured online activities, interactive feedback, collaborative practice, and engagement-oriented learning tasks to support students’ writing development.